High-performance InAlN/GaN HEMTs on silicon substrate with high fT × Lg. (4th September 2019) - Cui, Peng; Mercante, Andrew; Lin, Guangyang; Zhang, Jie; Yao, Peng; Prather, Dennis W.; Zeng, Yuping
Abstract: We report an 80 nm gate-length In0.17 Al0.83 N/GaN high-electron mobility transistor (HEMT) on silicon substrate with a record low gate leakage current of 7.12 × 10 −7  A mm −1, a record high on/off current ratio of 1.58 × 10 6, and a steep subthreshold swing of 65 mV dec −1, which are excellent features among the reported InAlN/GaN HEMTs on Si. Due to the excellent DC performance, a current gain cutoff frequency f T of 200 GHz is achieved, resulting in f T  ×  L g  = 16 GHz μ m for GaN HEMTs on Si which to the best of our knowledge is a new record.